Isolation and Characterization of Lactic Acid Bacteria from Fermented Milk Produced in Jimma Town, Southwest Ethiopia, and Evaluation of their Antimicrobial Activity against Selected Pathogenic Bacteria - Tigistu Goa; Getenet Beyene; Mekidim Mekonnen; Kasahun Gorems (International Journal of Food Science)
Background. Raw milk is usually contaminated with pathogenic bacteria. Fermentation of milk is important to inhibit the growth of contaminants, spoilage, and pathogenic bacteria. The objective of this study was to isolate lactic acid bacteria from fermented milk and evaluate their antimicrobial activity against selected pathogenic bacteria. Methods. Laboratory-based experimental study design was conducted from May-July, 2021.Three samples of Ergo (each of 250 ml) were collected from Jimma town. Lactic acid bacteria (LAB) isolates were identified through integrated phenotypic techniques. Further identification was conducted through using API 50 CHL strips. Antimicrobial activities (AMAs) of LAB isolates were tested against clinical isolates of E. coli, S. aureus, and Salmonella spp. using agar well diffusion method. The data were analyzed by using SPSS software version 21 and Microsoft Excel spreadsheet. Tables and figures were applied to describe characteristics of data. Results. Twelve LAB isolates were identified. Those LAB isolates include six Lactococcus lactis subsp. lactis, Lactobacillus acidophilus (2), Lactiplantibacillus plantarum (1), Limosilactobacillus fermentum (2), and Leuconostoc lactis (1). Based on primary screening of LAB, isolates/strains ESCIa, ESBIa, and ESCIc show strong AMA against S. aureus, E. coli, and Salmonella spp. The CFS of ESCIc showed the highest AMA against S. aureus and Salmonella spp. with a zone of inhibition of 14.12±1.6 mm and 12.9±3.6 mm, respectively, while ESBIa showed the highest AMA against E. coli with a zone of inhibition of 13.5±2.1 mm. The CFSs of selected LAB strains were heat tolerant at varying temperatures up to 100°C. The CFSs of selected LAB strains were inactivated by proteinase enzymes, but they are not inactivated with amylase enzymes. Conclusions and Recommendation. All 12 LAB isolates exhibited antimicrobial activity against tested bacterial strains. Lactobacillus isolates showed the highest antagonistic activity on tested indicator strains. Thus, they are possible alternatives to antibiotics in the era of antimicrobial resistance. S. aureus was the most sensitive to antimicrobial effects/agents of selected LAB isolates. Consumption of fermented foods is advisable since they support the growth of healthy GIT microbiota. Fermentation serves as biopreservation of food. However, analysis of probiotic features and in vivo probiotic effects of those LAB isolates will be subject of future research/study.